Crossmodal compensation: sensory discomfort affects consumer preferences across modalities - Groth, O; Hadi, R; Block, L (Wiley, 2024)
Consumers are frequently exposed to uncomfortable sensory circumstances (e.g., hot weather and noise pollution), yet little research has examined how such discomfort might systematically shape preferences. Drawing from research on crossmodal associations, we propose and empirically support a discomfort-driven crossmodal compensation effect in which consumers exposed to uncomfortable atmospheric sensations in one modality (e.g., loud noise) compensate through product choices across other modalities (e.g., choosing visually “quiet” products). Across five studies, we document the consequences of this phenomenon on actual (studies 1 and 2) and hypothetical (studies 3, 4, and 5) consumer choices and preferences. Further, we demonstrate that a desire to reduce sensory discomfort drives this crossmodal compensation effect, and the spillover only manifests when individuals are unable to adjust within the initially disturbed modality. Our research contributes to the literature on goal theory and crossmodal associations by demonstrating that discomfort experienced in one modality can systematically affect product preferences in other modalities.